The Enhancement of Batu Lanchang Vocational College Students’ Learning Style and Motivation via Psychoeducational Group Counseling during COVID-19 - Nazri Noorsyahika Mohamed; Abu Bakar Abu Yazid (Universitas Pendidikan Ganesha, 2023)
This study aims to explore the learning style and motivation of Batu Lanchang Vocational College students during the COVID-19 pandemic. This study involved five students studying at Batu Lanchang Vocational College, Pulau Pinang, Malaysia. This study uses both qualitative and quantitative methods. It is conducted during three psychoeducational sessions. Data analysis using content analysis techniques. The results found that the respondent's learning style is not bound to one style only and it is diverse. But it depends on the convenience and comfort of the respondent (dominant). From the aspect of motivation, respondents are more inclined to intrinsic motivation which is internal motivation because they want to achieve goals based on internal desire. Next, the relationship between learning style and student motivation is that respondents have experiences that can be used as motivation and reinforcement, namely intrinsic motivation, there is a relationship between learning style and student motivation. The findings give a good effect on students for students to choose their learning style better.